Made and Created in China: Super Processors and Two-way Heterogeneity - Zhiyuan Chen; Aksel Erbahar; Yuan Zi (Tinbergen Institute, 2019)
In this paper, we show that there exists a special breed of firms that are active in both ordinary and processing exports. Contrary to the existing literature that describes processing firms as inferior, these mixed firms are superior to other firms in multiple dimensions, and hence we call them "super processors." We build on Antràs et al. (2017) and Bernard et al. (2019) to develop a model in which firms are heterogeneous in multiple stages of production. Firms endogenously choose to become suppliers or final good producers, and those that excel in both manufacturing ability and blueprint quality choose to engage in both activities. We test our model's central prediction by exploiting China's pilot "paperless" processing trade supervision program that lowered the cost of processing trade but left ordinary trade costs unchanged. We find that facilitating processing exports induces productive domestic downstream firms to establish their own trademarks. Our results highlight that processing trade not only leads goods to be "Made in China," but also "Created in China."
Keywords: F14; F12; F13; 330; heterogeneous firms; production networks; trade policy; processing trade; China